PENDAMPINGAN GURU SD DALAM MENGEMBANGKAN BAHAN AJAR SANITASI BERBASIS AI DI WILAYAH PEMBANGUNAN 1 KABUPATEN JAYAPURA - Sarima, Sarima; Ashari, Makmum; Pistanty, Mingle A (Universitas Mataram, 2025)
Sanitation remains a persistent challenge in elementary schools in Jayapura Regency, particularly in Waibu and Sentani Districts. Limited facilities combined with low awareness among teachers and students have negatively affected both health and learning quality. This community engagement program sought to strengthen elementary school teachers’ capacity to design Artificial Intelligence (AI)-based sanitation teaching materials through a Continuous Professional Development (CPD) framework. Thirty teachers from twelve partner schools participated in training, mentoring, and evaluation sessions. The initiative produced 20 draft teaching modules, of which 12 schools successfully applied them in classroom settings. Teachers’ competencies showed a marked improvement, as reflected in the increase of average scores from 76 (pre-test) to 89 (post-test). Classroom observations also demonstrated greater student engagement in sanitation practices, such as proper handwashing and waste disposal. These findings highlight that AI-based teaching materials are both feasible and effective for promoting contextual sanitation education in resource-constrained schools. Nevertheless, persistent challenges related to limited devices, unstable internet connectivity, and inadequate sanitation infrastructure underscore the need for extended mentoring and stronger support from local authorities.